(untitled) (Proceedings of International Conference on Special Education, 2015)
Every child, including children with special needs, is guaranteed of their right to receive educational service. Said educational service has to be available, and affordable. Regardless of physical, mental, social, economic and geographic obstacles, educational rights should be fulfilled without any discrimination (Regulation of National Education System, Number 2, 2003). Ministry of National Education has stipulated Minister Regulation Number 70, 2009 concerning inclusive education. Several regencies have initiated to realize the policy. How far the policy has been realized? Research team from UNESA University in corporation with SEBELAS MARET University has organized research in three districts, which are Surakarta that has executed three years of implementation, Gresik that has executed two years of implementation, and Batu that has executed one year of implementation. Research result showed significant progress in achievement and actualization of inclusive education in said three districts. Innovation and support from stakeholders, and also utilization of local resources, aid to facilitate its progress. The progress can be presented in qualitative and quantitative indicators.